Clinicopathologic Significance of BRAF Mutation and Extracellular Signal Regulated Kinase 1/2 Expression in Patients With a Colorectal Adenocarcinoma - Kim, Hyung Ook (Ann Coloproctol, 2015)
PURPOSE: BRAF mutation and expression of extracellular signal regulated kinase (ERK) are linked with colorectal carcinogenesis through the serrated pathway. BRAF and ERK1/2 play important roles in the activation of mitogen-activated protein (MAP) kinase signaling pathways. The present study investigated the clinicopathologic outcomes of BRAF mutation and ERK1/2 expression in patients with colorectal cancer (CRC) and the possibility of using them as prognostic indicators. METHODS: Dual-priming oligonucleotide-based multiplex polymerase chain reaction for BRAF(V600E) mutation and immunohistochemical analysis of ERK1/2 were performed using 65 formalin-fixed, paraffin-embedded samples from patients with CRC. We analyzed the dependences of the clinicopathologic features on BRAF mutation and ERK1/2 expression. RESULTS: Out of 65 samples from CRC patients, BRAF mutation was detected in 3 (4.6%). The 3 patients with BRAF mutation presented with T3 CRC with lymph node metastasis (stage III) showing moderately or poorly differentiated histology. ERK1 and ERK2 were positively detected in 73.8% and 15.4% of the patients with CRC, respectively. ERK1 expression was significantly correlated with lymph node metastasis (P = 0.049). ERK2 expression was significantly correlated with tumor emboli (P < 0.05), tumor invasion (P = 0.035), lymph node metastasis (P = 0.017), and stage (P = 0.02). CONCLUSION: BRAF mutation and ERK1/2 expression may be associated with advanced or more aggressive CRC. These molecular markers might play prognostic roles in CRC developed through the serrated pathway.